Sickness absence: a pan-European study - Livanos, Ilias; Zangelidis, Alexandros (Munich, 2010)
"This study, using the EU-LFS, examines the determinants of sickness absence in 26 EU countries. The analysis highlights the importance of demographic and workplace characteristics and of institutional and societal conditions. Female workers aged 26-35 exhibit higher absenteeism, possibly reflecting the level of high household labour pressure. Increased job insecurity, captured by temporary contracts, and labour market uncertainty, reflected in higher unemployment rates, have a negative effect on absenteeism. Finally, individual sickness absence is lower in countries with higher proportion of dependent/out of the labour market individuals, probably because of the increasing pressure labour active people may experience."